A highly flexible, electrically conductive, and mechanically robust graphene/epoxy composite film for its self‐damage detection. Issue 34 (20th January 2020) - Meng, Qingshi; Kenelak, Vincent; Chand, Aron; Kang, Hailan; Han, Sensen; Liu, Tianqing
Abstract: Advanced functional composites have attracted a great attention for fabricating flexible devices. In this article, the GnP/epoxy composite film was prepared by mixing graphene platelets (GnPs) with epoxy through sonication process. The morphology, mechanical properties, and electrical conductivity of the prepared composites were investigated. As the GnP contents increased from 2.5 to 7.5 vol%, the composites showed an increase in strain sensitivity with the rapid decrease in the strain gauge to 4.4. Additionally, when dynamic movement of the flexible film was performed, at bending and twist angle of 135° and 180°, respectively, steady increase in both resistance changes were detected and compared. The electrical resistance of the flexible was measured over a temperature range of 20–95°C, an increase in temperature lead to a linearly equivalent increase in resistance. The composites can also detect slight pressure changes at 2 kPa compression force with rapid decrease of resistance. Additionally, fatigue test was performed with stable, sensitive, and no distinguishable reading under 2, 000 stretching cycles. The composite film exhibits an excellent self‐sensing responds when fracture occurred. Thus, the obtained highly flexible, conductive, and mechanical robust composite sensor can be applied as advanced composites sensors for health monitoring. Abstract :